Long bones, a slaughterhouse by-product, may serve as an excellent source for mesenchymal stem cells - SANTRA, LAKSHMAN; GUPTA, SAURABH; KANNAN, SANGEETHA; SINGH, AJAY K; KUMAR, GVPPS RAVI; NASKAR, SOUMEN; GHOSH, JYOTIRMOY; DHARA, SUJOY K (The Indian Journal of Animal Sciences, 2017)
Mesenchymal stem cells (MSCs) are one of the rarest sub-populations of bone marrow resident cells having inherent ability to differentiate into mesenchyme tissues e.g. bone, cartilage and adipose tissues. The natural selfrenewal ability and potential for lineage specific differentiation have made these cells an excellent material for research and therapy in regenerative medicine. But, successful isolation and in vitro expansion of these cells still remain the pivotal steps for majority of stem cell based applications. Various techniques have been successfully used for isolation of MSCs from laboratory animals, but those are difficult to apply for domestic species. Hence, harvesting MSCs from most domestic animals remains a real challenge. Here we have demonstrated an easy, convenient, low cost method of MSCs isolation from slaughtered animals. As a proof of concept, MSCs were isolated from bone marrow of 3 different species, namely, sheep, pig and goat. These cells expressed multiple markers and also retained their self-renewal potential, exhibited by successful sub-culturing over 30 passages. Moreover, MSCs expressed many pluripotency factors e.g. OCT4, Nanog, c-Myc, KLF2 and KLF4. This indicated that the bone marrow derived MSCs were at very early stage of commitment and therefore, possibly retained high plasticity. Since these cells are available from slaughtered animals, this circumvents the bioethical issues associated with invasive method of MSC isolation from bone marrow. This invaluable and easily adoptable method for isolation of MSCs from large domestic animal would encourage isolation process in other animals and help in future cell based researches and therapies in the field of regenerative medicine.